Instant milk powder production : determining the extent of agglomeration : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemical Technology at Massey University, Palmerston North, New Zealand - Williams, Anna M. (Massey University, 2007)
Agglomerated milk powders are produced to give improved properties such as flowability, dispersibility, reduced dustiness and decreased bulk density. A key function of these powders is to dissolve "instantly" upon addition to water and because of this they are also called "instant milk powders". They are produced by agglomerating the undersized fines that are returned to the top of the spray drier with milk concentrate droplet spray. Interaction occurs in a collision zone, often with multiple sprays and fines return lines. Agglomeration can be a difficult process to control and operators find it hard to fine tune the process to produce specific powder properties. This work aimed to understand the effects of key droplet and fines properties on the extent of agglomeration to allow a mechanistic understanding of the process. Three scales of spray drier were investigated in this study with different rates of evaporation; a small scale drier (0.5 - 7 kg water h-1), a pilot scale drier (80 kg water h-1) and a range of commercial production scale driers (4 - 15 000 kg water h-1). A survey of operators of commercial scale driers showed that control of instant milk powder production to influence bulk density is highly intuitive. Fines recycle rates were expected to be important in control of agglomeration processes and were estimated on a specific plant by using the pressure drop measured in the fines return line. A model based on pressure drop along a pneumatic pipeline under-predicted the experimental values for pressure drop due to solids, which means a calibration curve should be generated for each specific drier. Fines recycle rates were predicted to be significantly higher at 95 to 130 % of production rates compared to those expected by operators of 50%. Experimental measurements agreed with existing models for the effect of temperature on the density and viscosity of milk concentrates. Experimental results showed that the surface tensions of concentrated milks were within the same range as literature values for standard milks below 60°C, but were significantly higher for milk above 60°C. This is thought to be linked to the mechanism of skin formation due to disulphide cross linking at high temperatures and concentrations. Powder properties were also established for selected products produced on the commercial scale driers. These powders were then used in experiments on the two smaller driers. Because collision frequency depends on the velocity and droplet size of sprays; these properties were measured for the small scale drier and estimated, where possible, for the pilot and commercial driers. The small scale agglomerating spray drier was configured to alter droplet and particle properties when interacting a vertical fines particle curtain with a horizontal spray sheet. An extensive design and improvement process was carried out to ensure the system consistently delivered these streams in a controllable manner. The processes of collision and adhesion occur very quickly inside the spray drier. In order to assess the extent of agglomeration that has occurred, the feed streams must be compared to the final product stream. An ideal way to do this is to use an agglomeration index which compares the particle size distributions of the feed (fines recycle and spray streams) and the particle size distribution of the product stream (the agglomerated powder). The index described changes between these steams across the particle size distribution and is called an agglomeration efficiency, ξg. However, it was found that the presence of fines in the product of the one-pass design obscured the agglomerates formed. The agglomeration efficiency, ξg, was modified to become ξh which subtracted the fines stream from the agglomerated product distribution. In this way ξh models industrial operation where the fines are recycled, by effectively just comparing the spray and product streams entering and leaving the process. The small scale drier was used for an experimental study on natural and forced agglomeration, where the drier was operated with spray only, then with spray and fines. For natural agglomeration, SEM images of the product powder indicated that little agglomeration occurred between spray droplets. The product yield was unacceptably low (~ 40%) due to adhesion of spray droplets to the drying chamber wall opposing the horizontal spray. When the fines curtain was introduced in the forced agglomeration experiments, product yield increased above 50% because the fines acted as collectors for the spray droplets. However, the agglomeration performance of the modified spray drier was lower than expected. The equipment design was then optimised by considering three key issues; fines dispersion, droplet dispersion and stickiness, and agglomerate breakdown. Final experiments studied agglomeration at low fines to spray mass flux ratios and showed that increasing the fines size had a positive effect on agglomeration efficiency,ξh. The agglomeration study at pilot scale identified the effect of key variables, total solids, concentrate and fines flow rate, and fines size on the agglomeration efficiency. A dimensionless flux approach was used to explain the experimental results. The fines to spray mass flux ratio and the projected area flux ratio (at constant concentrate flow rate) were found to be the most suitable to represent the physical processes during agglomeration. Experimental results showed that a higher dimensionless flux resulted in more agglomeration and as well as small fines size and atomising low solids concentrate. The critical Stokes number highlighted the importance of particle size and collision velocity on the outcome of the collision as well as the importance of stickiness on adherence following the collision. A statistical analysis established a relational model for predicting the agglomeration efficiency based on fines size, total solids and the fines to spray mass flux ratio. This thesis has gained insight into agglomeration processes during spray drying and knowledge about how to define the extent of agglomeration. Practical findings from this research can have a significant impact on successful spray drying operation for instant powders. There are some practical steps to be taken industrially to promote the control of agglomerating spray driers. The first step is to measure and control the flow of fines recycled to the top of the spray drier. The next step is to validate the findings at industrial scale and link the agglomeration index to the bulk powder properties. However, there are many challenges that remain to be tackled in the area of milk powder agglomeration. Milk powder agglomeration at the top of the spray drier is a complex process involving many different variables. A more detailed study of the micro processes that occur during agglomeration will give increased understanding of the relationships between key operating variables and agglomerate properties.
Keywords: Dried milk; Milk powder processing; Agglomerated milk powders; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290103 Food processing